Optimization of enzyme-assisted extraction of ginsenoside Rb1 from Vietnamese Panax notoginseng (BURK.) F.H. Chen roots and anticancer activity examination of the extract. Issue 10 (3rd July 2021) - My, Phan Le Thao; My, Huynh Thi Kieu; Phuong, Nguyen Tran Xuan; Dat, Tran Do; Thanh, Vuong Hoai; Nam, Hoang Minh; Thanh Phong, Mai; Hieu, Nguyen Huu
ABSTRACT: In this study, the conditions of ginsenoside Rb1 extraction from Panax notoginseng (Burk.) F.H. Chen ( P. notoginseng ) roots by enzyme-assisted method were investigated by using the central composite design (CCD). This design was applied to survey the effects of pH, temperature, and time on Rb1 content. The concentration of Rb1 was determined based on high-performance liquid chromatography (HPLC). The investigation of anticancer activities of P. notoginseng extract on breast carcinoma (MCF-7) cell lines and human lung carcinoma (Lu) showed that the extract had remarkable cytotoxic activity against these cancer cell lines.